2004
DOI: 10.1126/science.1092674
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the Paternal X Chromosome in Early Mouse Embryos

Abstract: It is generally accepted that paternally imprinted X inactivation occurs exclusively in extraembryonic lineages of mouse embryos, whereas cells of the embryo proper, derived from the inner cell mass (ICM), undergo only random X inactivation. Here we show that imprinted X inactivation, in fact, occurs in all cells of early embryos and that the paternal X is then selectively reactivated in cells allocated to the ICM. This contrasts with more differentiated cell types where X inactivation is highly stable and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
526
2
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 487 publications
(554 citation statements)
references
References 19 publications
18
526
2
8
Order By: Relevance
“…(3) The two studies concur that paternal X inactivation in preimplantation embryos is incomplete, with near complete silencing of genes closest to the XIC and partial or absent silencing of genes farther away from the XIC. (1,3) The unfinished nature of X p silencing in early development would presumably result in higher expression levels for some genes in females. This could explain the previously reported bimodal expression of some X-linked genes in mixtures of male and female preimplantation embryos.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…(3) The two studies concur that paternal X inactivation in preimplantation embryos is incomplete, with near complete silencing of genes closest to the XIC and partial or absent silencing of genes farther away from the XIC. (1,3) The unfinished nature of X p silencing in early development would presumably result in higher expression levels for some genes in females. This could explain the previously reported bimodal expression of some X-linked genes in mixtures of male and female preimplantation embryos.…”
Section: Introductionmentioning
confidence: 74%
“…Previous studies had suggested that genes may be expressed at a lower level from the X p in preimplantation embryos. (11)(12)(13) The current papers (1)(2)(3) that we discuss here further challenge the view that both X chromosomes are expressed in early stages of development by providing clear evidence of X p inactivation in preimplantation embryos.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations